2012
DOI: 10.1590/s1415-47572012005000049
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of α-thalassemia 3.7 kb deletion in the adult population of Rio Grande do Norte, Brazil

Abstract: α-Thalassemia, arising from a defect in α-globin chain synthesis, is often caused by deletions involving one or both of the α-genes on the same allele. With the aim of investigating the prevalence of α-thalassemia 3.7 kb deletion in the adult population of Rio Grande do Norte, 713 unrelated individuals, between 18 and 59 years-of-age, were analyzed. Red blood cell indices were electronically determined, and A2 and F hemoglobins evaluated by HPLC. PCR was applied to the molecular investigation of α-thalassemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
(41 reference statements)
0
8
0
1
Order By: Relevance
“…For α-thalassemia, the most common deletion encountered in sub-Saharan Africa is a deletion of 3.7 kb (α −3.7 deletion) resulting in an α-globin synthesis defect [25]. The gene deletion of 3.7 kb was detected by multiplex PCR with a method adapted from Liu et al [34] and according to the GoTaqFlexi DNA Polymerase (Promega) requirements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For α-thalassemia, the most common deletion encountered in sub-Saharan Africa is a deletion of 3.7 kb (α −3.7 deletion) resulting in an α-globin synthesis defect [25]. The gene deletion of 3.7 kb was detected by multiplex PCR with a method adapted from Liu et al [34] and according to the GoTaqFlexi DNA Polymerase (Promega) requirements.…”
Section: Methodsmentioning
confidence: 99%
“…The most common deletion encountered in sub-Saharan Africa is a deletion of 3.7 kb (α −3.7 deletion). The heterozygous carriage of this deletion (α −3.7 thalassemia trait) is not or only slightly symptomatic, but homozygous deletion can cause hematological alterations or be lethal [25].…”
mentioning
confidence: 99%
“…In particular, in southeastern Brazil, a frequency of 1.3% of b-thalassemia trait carriers (BTC) was reported in the general population (10), while a-thalassemia trait carriers (ATC), determined by a 3.7-kb DNA deletion (-a 3.7 /aa), varied from 20 to 25% in Brazil's African descents (11) and 9 to 12% in general population. Previous studies have shown that the -a 3.7 is the most frequent a-globin gene deletion in Brazil (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…α-Thalassemia is estimated to affect around 5% of the population worldwide, with the -α 3.7 deletion being the most common alteration ( Piel and Weatherall, 2014 ). In Brazil, its prevalence is high ( Sonati et al , 1991 ; Couto et al , 2003 ; Adorno et al , 2005 ; Wagner et al , 2010 ; Cardoso et al , 2012 ; De Medeiros Alcoforado et al , 2012 ). However, Hb H disease, which is found primarily in Southeast Asia, the Middle East and the Mediterranean, has only rarely been reported in Brazil, where most cases are the result of an interaction of the -α 3.7 deletion with the -- MED , -(α) 20.5 , or -- SEA deletions ( Sonati et al , 1992 ; Wenning et al , 2000 , 2002 , 2009 ; Kimura et al , 2009 ).…”
mentioning
confidence: 99%